Ammi Analysis for Yield and Stability in Direct Seeded Rainfed Rice (Bangladesh Journal of Botany, 2022)
The genotype × environment interaction and stability performance of 15 rice landraces was studied using the additive mean effects and multiplicative interaction (AMMI) analysis. The overall, results indicated that significant genotype × environmental interaction (GEI) influenced the relative ranking of the rice landraces across the years/seasons. It was evident from AMMI analysis that first two principal components accounted for 91.90%, which is enough to explain the variability among the landraces. The landraces, G8 (Kallurundaikar), G4 (Sivapuchithiraikar) and G5 (Kuruvaikalanjiyam) exhibited high grain yield. The AMMI 2biplot revealed that the rice landraces, G12 (Poongar), G14(Kala namak) and G15 (Kichali samba) are close to the origin indicating non sensitive nature of these genotypes with the years/seasons and highly stable genotypes across the environments with low yield potential when compared to others. According to the polygon view of GGE biplot, the genotype G8 (Kallurundaikar) was the winner in the environments E2 and E5 whereas the genotypes G5 (Kuruvaikalanjium) and G7 (Mattaikar) were the winners in the environment E1, E3 and E4. The landrace, G8 (Kallurundaikar), has high mean yield with stable performance over five environments being the overall best and it may be considered for the direct seeded rice cultivation in the rainfed ecosystem.Bangladesh J. Bot. 51(3): 469-475, 2022 (September)